The Amulet of Samarkand - Stroud, Jonathan (New York : Hyperion Books For Children, 2003)
Nathaniel, a magician's apprentice, summons up the djinni Bartimaeus and instructs him to steal the Amulet of Samarkand from the powerful magician Simon Lovelace.
Keywords: Magic -- Fiction; Wizards -- Fiction; Apprentices -- Fiction; Genies -- Fiction; London (England) -- Fiction; England -- Fiction